Effect of Urea Fertilizer on the Biochemical Characteristics of Soil - Shetty, Premalatha; Acharya, Chaithra; Veeresh, Nalavi (International Journal of Applied Sciences and Biotechnology, 2019)
Urea-potash mixture was added to the manured soil at three different concentrations equivalent to 0.8, 1.6 and 2.4g f urea per 10Kg of soil. Nitrate and nitrite N concentration in the soil increased within 24h after addition of urea. The nitrate N content in soil without urea was 17 µg and in urea fertilized soils, it ranged from 39.9-47 µg/g of soil after 19h. . Increase in total mineralizable N was around 67- 160% in urea fertilized soils in comparison to the control. Percent conversion of urea to nitrate and nitrite N decreased at higher concentrations of the fertilizer. Addition of biochar to urea amended soil did not bring about significant change in the available N content. Decrease in total mineralizable N and accumalation of available P was observed over the period of 15 days. Addition of urea resulted in acidification of the soil. Acidification of the soil could be correlated with increase in acid phosphatase concentration. The soil amended with biochar exhibited significant buffering capacity in the region of pH 7.4-9. Int. J. Appl. Sci. Biotechnol. Vol 7(4): 414-420